2009
DOI: 10.1002/marc.200800690
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Lipase‐Catalyzed Synthesis of Polyesters

Abstract: Polyester synthesis by lipase catalyst involves two major polymerization modes: i) ring-opening polymerization of lactones, and, ii) polycondensation. Ring-opening polymerization includes the finding of lipase catalyst; scope of reactions; polymerization mechanism; ring-opening polymerization reactivity of lactones; enantio-, chemo- and regio-selective polymerizations; and, chemoenzymatic polymerizations. Polycondensation includes polymerizations involving condensation reactions between carboxylic acid and alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
212
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(220 citation statements)
references
References 234 publications
7
212
0
1
Order By: Relevance
“…This is in agreement with enzymatic ring opening mechanisms where the lipase tends to first ring open the monomer (lactone) to its corresponding hydroxy acid which leads to low M n , however, high PDI (18). Subsequent chain propagation and build up of oligomers lead to higher M n of the polymer while decreasing its PDI (18). Reported literature of lipase catalysis of caprolactones showed that at higher conversions the PDI of the poly-caprolactone formed are about 2 (25,26), however, comparison of use of MW heating and thermal heating of caprolactone polymerization using chemical catalysts showed that the use of MW heating favors chain growth in the initial stage thus limiting the number of polymer chains, whereas thermal heating favors the formation of growing centers (22).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…This is in agreement with enzymatic ring opening mechanisms where the lipase tends to first ring open the monomer (lactone) to its corresponding hydroxy acid which leads to low M n , however, high PDI (18). Subsequent chain propagation and build up of oligomers lead to higher M n of the polymer while decreasing its PDI (18). Reported literature of lipase catalysis of caprolactones showed that at higher conversions the PDI of the poly-caprolactone formed are about 2 (25,26), however, comparison of use of MW heating and thermal heating of caprolactone polymerization using chemical catalysts showed that the use of MW heating favors chain growth in the initial stage thus limiting the number of polymer chains, whereas thermal heating favors the formation of growing centers (22).…”
Section: Resultssupporting
confidence: 86%
“…Figure 1 also indicates that in the region where higher M n chains of PCL are synthesized, the PDI of the polymer is low. This is in agreement with enzymatic ring opening mechanisms where the lipase tends to first ring open the monomer (lactone) to its corresponding hydroxy acid which leads to low M n , however, high PDI (18). Subsequent chain propagation and build up of oligomers lead to higher M n of the polymer while decreasing its PDI (18).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The application of enzymes is not limited to their original environment or natural role as such. In fact, their versatility facilitates their use in industrial applications, ranging from the food industry to pharmaceuticals, as well as in organic solvent-based polymerization processes [6].…”
Section: Introductionmentioning
confidence: 99%